The role of the neuregulin-1/erbb signaling pathway in cardiac morphogenesis and remodeling - Vasti, Cecilia (2014)
Neuregulin-1 (NRG1) signaling through tyrosine kinase receptors erbB2 and erbB4 was revealed essential for cardiac development as mouse mutated in the Nrg1 or either cognate receptors Erbb2 or Erbb4 genes lack the formation of trabeculae at the ventricular wall. Indeed, the injection of the NRG1 active peptide in developing embryos induced trabeculation of the ventricular free wall. The components of the NRG1 pathway have been identified and the cardiac activities are being progressively characterized. An acquired form of dilated cardiomyopathy was evidenced in a subpopulation of breast tumor patients undergoing a combined treatment with antibodies against erbB2 and chemotherapy. In this regard, the cardiomyocyte-specific gene deletion of either erbb2 or erbb4 leads to ventricular dilation in adult mice, providing an experimental model system to examine the NRG1-mediated activities. We reviewed the evidence on the growing field of research for NRG1 signaling in both cardiac morphogenesis and in the postnatal myocardial remodeling.